A melancolia nas crônicas de Maria Judite de Carvalho - Freitas, Olívia Rocha (2011)
Maria Judite de Carvalho began his literature in 1949 in journals of Lusitanian capital. Until his death, which occurred in 1998, published more a thousand texts, most of them have never been extracted from their support original, the newspaper, making them unknown to the public today. In order to rescue of this precious material chosen as the literary corpus of Search the chronicles published in the Diário de Lisboa, periodic where the writer published the largest number of texts in the section Rectângulos da Vida, 395 (three hundred and ninety-five) chronic for five consecutive years (1968-1972). Looking at these texts I realized that she inserted into her narrative the changes occurred in the twentieth century, in Portugal, capturing the moment of breaking with traditional models and introducing new paradigms imposed by modernity. What happens in this period is an extremely fast and deep change of values and customs with which the Portuguese society faces and experiences with a certain uneasiness. Given this unstable scenario, Maria Judite expresses, through her ironic and critical narrative, the portrait of the Portuguese people and their behavior full of anguish and sorrows that are revealed through the gloom. After a thorough reading of his texts I found that this was the guiding element of juditiana writing. It is presented in the chronicles in many respects they were privileged during the five years of publications they are loneliness, abandonment, death, isolation of individuals who feel increasingly powerless in the face of changes experienced as a consequence of this state and present is melancholy all the time. This is a photograph of Maria Judite de Carvalho on Portuguese society told in her chronicles as I saw this survey.